PENGARUH DEBT TO EQUITY RATIO (DER), RETURN ON ASSET (ROA), DAN EARNING PER SHARE (EPS) TERHADAP PRICE TO BOOK VALUE (PBV) PADA PERUSAHAAN TELEKOMUNIKASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2009-2013 - Suryaman, Maman; Khoirunnisa, Rikha Muftia (Jurnal Fokus Manajemen Bisnis, 2015)
This study aims to analyze the effect of Debt to Equity Ratio (DER), Return On Assets (ROA), and Earning Per Share (EPS) on Price to Book Value (PBV). The sample used was a telecommunications company listed on the Indonesia Stock Exchange in the 2009-2013 period, in which there were six companies. The statistical method used is a multiple linear regression model. From the results of the Classical Assumptions test that is a test for normality, autocorrelation, multicollinearity, and heterosecdasticity, followed by multiple linear regression testing. The results showed that simultaneously (simultaneously) the variable Debt to Equity Ratio (DER), Return On Assets (ROA), and Earning Per Share (EPS) significantly influence the Price to Book Value (PBV) with a significance of 0,000. While partially only Debt to Equity Ratio (DER) with a significance of 0,000, Return On Assets (ROA) with a significance of 0,000 that significantly influence the Price to Book Value (PBV). While Earning Press hare has no significant effect on Price to Book Value (PBV) with a significance level of 0.273.